Aeolian dust and diatoms at Roosevelt Island (Ross Sea, Antarctica) over the last 2 millennia reveal the local expression of climate changes and the history of the Ross Sea polynya - S. Lagorio; S. Lagorio; B. Delmonte; D. Tetzner; E. Malinverno; G. Baccolo; G. Baccolo; B. Stenni; M. Frezzotti; V. Maggi; N. Bertler; N. Bertler (Climate of the Past)
The pattern of atmospheric and climate changes recorded by coastal Antarctic ice core sites and the processes they illustrate highlight the importance of multiproxy studies on ice cores drilled from such peripheral areas, where regional- to local-scale processes can be documented. Here, we present a 2 kyr long record of aeolian mineral dust and diatoms windblown to Roosevelt Island, obtained from the Roosevelt Island Climate Evolution project (RICE) ice core. Mineral dust and diatoms are highly complementary at RICE, since they are related to the large-scale South Pacific atmospheric circulation regime, carrying dust-rich air masses that travelled above the marine boundary layer, and local oceanic aerosol transport by low-level marine air masses, respectively. The period from 550 to 1470 CE is marked by increased mineral dust transport from Southern Hemisphere continents, a reduction in sea ice cover in the Eastern Ross Sea (ERS) and Amundsen Sea (AS), and more frequent incursions of humid air masses, which contributed to a relative rise in snow accumulation. After 1470 CE, relatively lower dust and snow deposition at RICE suggests an increase in pack ice in the eastern Ross and Amundsen seas. This period is characterized by prominent peaks of sea-ice-related aeolian diatoms that are unprecedented over the last 2 kyr, indicating a rapid reorganization of atmospheric circulation. Data suggest an eastward enlargement of the Ross Sea polynya culminating with the opening of the proposed Roosevelt Island polynya and an increased influence of low-level marine air masses to the site during the Little Ice Age (LIA).